Réponses

2012-12-08T08:26:47+01:00

A = (x+1)² -2(x+1)

A= (x+1)(x+1) -2(x+1)

A = x² 2x +1-2x -2

A = x² -1

 

B= (2x+3)² +((x+2)(2x+3)

B= 4x² +12x +9 + 2x² +3x +4x +6

B= 6x² +19x +15

 

C= (3x-5)² -(x+4)(3x-5)

C= (9x² -30x +25) - ( 3x² -5x + 12x -20)

C= 9x² -30x +25 -3x² -7x +20

C= 6x² -37x +45

 

Bon courage !

2012-12-08T09:22:52+01:00

Bonjour

A = (x+1)²-2(x+1)

A = (x+1)(x+1)-2(x+1)

A = (x+1)(x+1-2) 

A =(x+1)(x-1) c'est la forme de (a+b)(a-b) = a²-b²

A = x²-1 

B = (2x+3)²+(x+2)(2x+3)

B = (2x+3)(2x+3)+(x+2)(2x+3)

B = (2x+3)(2x+3+x+2)

B = (2x+3)(3x+5) 

C = (3x-5)²-(x+4)(3x-5)

C = (3x-5)(3x-5-x-4)

C = (3x-5)(2x-9)